Etyczne aspekty zróżnicowania dochodów - Wyżnikiewicz, Bohdan (Annales. Etyka w Życiu Gospodarczym, 2019)
Personal income differentiation (inequality) is widely observed. Various historical and cultural factors are responsible for this phenomenon. In the longer run, these factors lead to a log-normal distribution of income with country-specific parameters. Ethical aspects of income differentiation are discussed in this paper. The starting point for the discussion is a diagnosis of income differentiation in Poland and European Union countries based on statistical data. Another discussed issue is ethical dilemmas resulting from income inequalities. Special attention is paid to the relationship between income differentiation and economic growth. The ethical aspects of the ratio between lower and upper income in corporations are also discussed. The conclusion is that income differentiation and its change may influence economic growth in different ways. Extremely high income differentiation may lead to negative effects and is ethically doubtful.